Colon Targeting by Novel Drug Delivery Drug System: Microsphere a Review Report - Choudhary, Priyanka (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
In the recent year, colonic drug delivery has gained importance for delivery of drug for the treatment of local diseases associated with colon and systemic delivery of therapeutic peptides and proteins. Treatment could be more effective if it is possible for drug to be directly delivered to colon. During the past decade, there are new developments in site-specific formulations for targeting drug to the colon. Colon has proved to be a site for the absorption of poorly soluble drugs. Microcarriers as colon drug delivery system have gained importance for the delivery of the drug in the colon because of their increase biocompatibility, controlled release of drug, and higher stability. This review is discusses in brief about introduction to colon, microcarrier as colon drug delivery system. Oral delivery is still the most favorable route of drug administration, especially for chronic therapies where repeated administration of drug is required. Oral administration offers less pain, good patient convenience, and reduced risk of cross infection and needle stick injuries.